The Limits of Language as the Limits of the World: Cormac McCarthy’s and David Markson’s Post-Apocalyptic Novels - Ambroży, Paulina (Text Matters: A Journal of Literature, Theory and Culture, 2015)
The article examines the correlation between the world and the word in two novels which engage with a post-apocalyptic scenario: David Markson’s Wittgenstein’s Mistress (1988) and Cormac McCarthy’s The Road (2006). Shifting the focus from the very event of catastrophe to the notion of survival through memory and storytelling, both novels problematize the strained relationship between language and reality in an increasingly diminished and dehumanized world. My aim is to investigate the limits of language as well as its capacity to withstand the chaos, loss, trauma, and death that follow the apocalypse. The issues to be considered include the influence of external experience on forms of communication, the role of central metaphors (the archive and the museum in Markson’s novel; cinders and the road in McCarthy’s) and their relation to the form of both novels, as well as the word’s (in)capacity to preserve human values and hopes. Both novels will be discussed as deconstructionist projects in which language becomes a habitat at once impossible and life-preserving: in Wittgenstein’s Mistress it plays the role of both home and prison, whereas in The Road it functions as messianic discourse which simultaneously carries, propels and extinguishes the human hope for a transcendental reality beyond the post-apocalyptic emptiness and doubt.